Evaluation of Neuropsychiatric Effects of Montelukast-Levocetirizine Combination Therapy in Children with Asthma and Allergic Rhinitis - Uğur Altaş; Zeynep Meva Altaş; Fırat Öz; Mehmet Yaşar Özkars (MDPI AG, 2023)
Drug-induced neuropsychiatric effects are important for disease management. We aim to evaluate the neuropsychiatric effects of montelukast-levocetirizine combination therapy in children. This descriptive study was conducted with children aged 2-5 years, diagnosed with asthma and allergic rhinitis, who began to receive montelukast and levocetirizine combination therapy. The respiratory and asthma control test for children (TRACK), Rhino Conjunctivitis Scoring System (RCSS), and common neuropsychiatric effects (irritable behavior, hallucinations, headaches, nightmares, sleep disorders, behavioral and mood disorder, restlessness, depression) were ascertained by the questionnaire applied before and 4 weeks after the treatment. Parents answered on behalf of their children. The most common finding before and after treatment was irritable behavior. While irritable behavior was observed in 82.4% (n = 56) of children before the treatment, this percentage was 63.2% (n = 43) after the treatment (p = 0.004). The percentage of children who developed at least one neuropsychiatric symptom after treatment was 22.1% (n = 15). There was no significant effect of age, gender, RCSS, TRACK, or allergy test positivity on the development of neuropsychiatric symptoms (p > 0.05). According to the results, at least one neuropsychiatric finding developed in approximately one in five children. Identifying risk factors will enable more careful treatment or consideration of alternative treatments for children at higher risk in the clinical follow-up period.